Модель накопления повреждений и развития сталостного разрушения в твердых сплавах - Шестаков, С.И.; Яковлева, Т.Ю. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
A new method has been suggested for the assessment of cyclic strength of hard alloys. The
method is based on the simulation of the development of the local plastic strain, which is observed
during incubation and active periods of fatigue failure and characterized by the accumulation of
scattered damages, crack initiation and propagation.